Per‐ and Polyfluoroalkyl Substances in Ducks and the Relationship with Concentrations in Water, Sediment, and Soil. (23rd September 2020) - Sharp, Simon; Sardiña, Paula; Metzeling, Leon; McKenzie, Rob; Leahy, Paul; Menkhorst, Peter; Hinwood, Andrea
Abstract: The present study examined the occurrence and concentration of per‐ and polyfluoroalkyl substances (PFAS) measured in game ducks (13 compounds), water, sediment, and soils (33 compounds) in waterways in Victoria, Australia. The study aimed to identify potential ecological and human health risks from measured PFAS concentrations. Four species of duck and samples of water, sediment, and soil were collected from 19 wetlands, which were chosen based on their popularity as hunting locations. The risks posed by 3 PFAS (perfluorooctanoic acid, perfluorohexane sulfonic acid [PFHxS], and perfluorooctane sulfonic acid [PFOS]) to the environment and human health were assessed using available national ecological and human health guidelines. A diverse range of short‐ and long‐chain carboxylic and sulfonic acids were found in the environment and in ducks. Concentrations were generally low and varied between wetlands, duck species, tissue analyzed (breast or liver), and environmental compartment (water, sediment, soil). Higher PFOS concentrations in water and sediments were observed at wetlands near sources of contamination (i.e., a defense base or urban environment). Elevated PFOS and PFOS + PFHxS concentrations in ducks were observed near local point sources but also at wetlands with no known point sources of contamination. There were clear differences in PFAS concentrations detected in duck tissues versus the environment, highlighting complexities of bioaccumulation, movement of animals, and spatiotemporal variation and raising questions about the relevance of using abiotic criteria to assess risk to biota. Human health risk assessment showed that only ducks inhabiting wetlands near local sources of PFAS were likely to pose a risk to consumers. Further studies are required to improve our knowledge of PFAS toxicokinetics and chronic impacts in biota to guide management decisions. Environ Toxicol Chem 2021;40:846–858. © 2020 SETAC